The Influence Of Customer Satisfaction And Price Reasonability In Building Customer Loyalty Of Logistics Service Companies - Kristiawan, Raditya Yogi; Abdi, Antonius Surjo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
-